Applying computational intelligence to musical acoustics - KOSTEK, Bożena (Archives of Acoustics, 2007)
The aim of this paper is to review some selected computational techniques that find application in acoustics and in particular to sound engineering. The presented research studies involved using artificial neural networks, rough set method, fuzzy logic, genetic algorithms and other soft computing techniques. The investigated problems are related to classification of musical instrument sounds, musical phrases recognition, intelligent music processing, computer control of classical pipe organ instruments, and quality assessment.